Pengembangan Video Pembelajaran Augmented Reality Berbasis Flashcard pada PAI dan Budi Pekerti Kelas IX SMP: Development of Flashcard-Based Augmented Reality Learning Videos for the Grade IX Junior High School Subject of Islamic Religious Education and Character Building - Weni Weni; Fadriati Fadriati; Gustina Gustina; Sirajul Munir; Lita Sari Muchlis (ITScience (Information Technology and Science), 2026)
This study was motivated by the limited availability of interactive, contextual, and engaging learning media for Islamic Religious Education (PAI) in Grade 9 junior high school classes, which has resulted in low student engagement and suboptimal learning outcomes. Advances in educational technology have encouraged the use of Augmented Reality (AR) as an innovative medium capable of presenting material in a more visual, interactive, and accessible manner. This study aimed to develop AR-based learning videos integrated with flashcards for the PAI and Character Education subject, encompassing needs analysis, media design, validity testing, and an evaluation of practical classroom application. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. Research instruments included observation sheets, interview guidelines, expert validation forms, and student response questionnaires. Data were analyzed using both qualitative and quantitative descriptive techniques. The AR-based learning videos with flashcards achieved an average validity coefficient of 0.95 (categorized as